PEREMPUAN MINANGKABAU DALAM PANGGUNG POLITIK - Lindayanti Lindayanti (Mozaik: Kajian Ilmu Sejarah, 2019)
Women in the Minangkabau indigenous community structure have a unique role. In the Minangkabau matrilineal custom system, women are placed ina central position. Minangkabau women have been portrayed as having played arole in the political arena in Minangkabau for a long time. This can be seen fromclassic Minangkabau stories such as kaba, tambo or myth. Many stories ofwomen's heroism are found. What is the relationship between the ideal level andreality in the politics of Minangkabau women? For example, "Keagungan BundoKanduang" depicted in the story of Cindur Mato from an ideal level coupled withMinangkabau women performing in various fields such as Putri Rahmah elYunusiyah also established several other women's schools as an effort to increasethe education level of women in Minangkabau.